Peran Core Self-Evaluation dan Dukungan Atasan terhadap Pengayaan Kerja Keluarga - Maudy Safira Ervinadi; Artiawati Artiawati; Darmawan Muttaqin (Psympathic : Jurnal Ilmiah Psikologi, 2020)
In recent years, the number of women workers has increased, it means women participate in both work and family roles together. Interaction between work family life can also provide benefits in improving the quality of work-family life if managed properly. Core self-evaluation and supervisor support are the factors that cannot be separated from work-family life. The purpose of this study is to examine the role of core self-evaluation and supervisor support in predicting work-family enrichment using quantitative research method and collecting data through questionnaire. Measurements used in this study were Work-Family Enrichment Scale, Core Self-Evaluation Scale, and Supervisor Support Subscale from the Social Support Scale include supervisor emotional and instrumental support. Data were collected from 113 employees aged 20-59 with at least one child. The result indicates that core self-evaluation and supervisor support are the predictors of work-family enrichment. However, instrumental support from supervisor is not a predictor of work-family enrichment. Work-family enrichment happens when the individual has a positive core self-evaluation and sensing that the individual got support from supervisor.